Regulation of Contracts for The Representation of Professional Players (Concept and Effects) - فريـد, نصـر أبو الفتـوح (Journal of Legal Sciences, 2019)
Regulation of contracts for the representation of professional players has great theoretical and practical importance; The FIFA has issued a new regulation to deal with football intermediaries instead of the previously exist provision of the former players' agents. The FIFA also committed the national associations to use these new regulations through issuing new national provisions. Regarding the international and national regulations, we address the meaning of the football intermediaries, the characteristics of the contracts concluded by such intermediaries and its legal provisions, the rights of the football intermediaries, and the obligations incumbent on them.